956 Retained Appendiceal Tip and Abdominal Wall Appendicolith - A Rare Combination of Post Appendicectomy Complications. (12th October 2021) - Dey, A; Symons, N
Abstract: Appendicitis involving the appendix stump is a recognised post appendicectomy complication but the same involving the appendiceal tip is rare. Similarly, abdominal wall abscess secondary to retained appendicolith is also infrequently encountered. Our case highlights a rare combination of both complications arising separately. A 29-year-old man presented with 3 days of generalised malaise and progressively worsening right iliac fossa pain some ten months after a laparoscopic appendicectomy. This had been complicated by residual right iliac fossa inflammation that was treated conservatively and serial scans demonstrated gradually resolving inflammation. He also had well controlled ulcerative colitis. On examination, he was noted to be pyrexial with a tender fluctuant mass in the right flank. An ultrasound scan demonstrated inflammatory changes in the abdominal wall with no intra-abdominal collections. A diagnostic laparoscopy found an inflamed appendix tip, attached to the residual mesoappendix and embedded in the abdominal wall behind the mid-ascending colon. A completion appendicectomy was performed. The patient recovered well but returned 4 months later with persistent pain and a fluctuant mass over the right iliac fossa. Radiological investigation revealed an abdominal wall collection containing a calcified appendicolith. The collection was refractory to ultrasound guided drainage and an exploration of the abdominal wall allowed extraction of the appendicolith followed by symptomatic relief. This case emphasizes the importance of complete excision of the appendix and extraction of debris, which can be challenging when the appendix lies in a retro-colic position.